(untitled) (Research, Society and Development, 2019)
The aim of this study is to understand the role of nurses in the early diagnosis of breast cancer, to describe the actions and strategies used for this purpose and to know their perceptions about their role in this situation in a Basic Health Unit in the Municipality of Juazeiro-BA. This is a qualitative research of descriptive characteristics, with all nurses in zone IV of the city of Juazeiro-BA. After data collection, the data were grouped and analyzed using the Bardin method. The results showed that the professionals present knowledge about breast cancer and its screening, however, still deficient and confusing. There is a need for public policies that prioritize the training of professionals so that it can reflect on the improvement of health indicators.